2021
DOI: 10.1096/fba.2021-00077
|View full text |Cite
|
Sign up to set email alerts
|

Friends and foes: Extracellular vesicles in aging and rejuvenation

Abstract: Extracellular vesicles (EVs) are released by many different cell types throughout the body and play a role in a diverse range of biological processes. EVs circulating in blood as well as in other body fluids undergo dramatic alterations over an organism's lifespan that are only beginning to be elucidated. The exact nature of these changes is an area of active and intense investigation, but lacks clear consensus due to the substantial heterogeneity in EV subpopulations and insufficiencies in current technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 161 publications
(388 reference statements)
1
18
0
Order By: Relevance
“…A study that investigated mouse plasma EVs has shown an age-related decrease in lipoproteins but an increase with age of specific types of EVs using western blot analysis [ 34 ]. Given that the plasma particles analyzed by NTA contain lipoproteins, the finding by another study by NTA of an age-associated decrease of particle numbers in human and rodent plasma may be affected by an age-related decrease in lipoproteins [ 35 ]. Similarly, the particles analyzed by NTA in our study may contain lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…A study that investigated mouse plasma EVs has shown an age-related decrease in lipoproteins but an increase with age of specific types of EVs using western blot analysis [ 34 ]. Given that the plasma particles analyzed by NTA contain lipoproteins, the finding by another study by NTA of an age-associated decrease of particle numbers in human and rodent plasma may be affected by an age-related decrease in lipoproteins [ 35 ]. Similarly, the particles analyzed by NTA in our study may contain lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…As previously introduced, in the last decades it has been widely recognized that EVs secreted from senescent cells can transfer the aging phenotype to the recipient cells by regulating their gene expression or changing their energy metabolism [146]. To date, just some studies underline the properties of specific EVs in delaying aging processes.…”
Section: Anti-aging Potential Of Evs From Various Sourcesmentioning
confidence: 99%
“…Recent data from J. A. Fafian-Labora and colleagues [146] demonstrate the potential of small EVs isolated from primary fibroblasts of young human donors (sEV-Ys) as regenerative therapy in aging. Specifically, they reported that sEV-Ys possess glutathione-S-transferase (GST)-intrinsic activity and ameliorated cellular biomarkers of senescence by increasing the antioxidant capacity of old fibroblasts both in vitro and in vivo in old mice [146].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…For instance, mi-RNAs such as mi-RNA-21/ 29/ 34 modulate regeneration and tissue functionality by targeting various tissues and involving different pathways which might interfere with long life expectancy (127). Despite, substantial changes to extracellular vesicles with age, it is not clear whether these changes represent a cause or effect of aging or associated comorbidities (128). On the contrary, the role of exosome in HIV infection is critical since this pathway releases intracellular material and exchanges material and information between cells.…”
Section: Extracellular Vesicles (Exosomes)mentioning
confidence: 99%